Impact of Hardware Choice on Talonavicular Arthrodesis Non-Union Rate. Issue 4 (22nd October 2020) - Corr, Daniel; Kothari, Parth; Pedowitz, David I.
Category: Midfoot/Forefoot; Ankle Arthritis; Hindfoot Introduction/Purpose: Talonavicular arthrodesis is a commonly performed procedure in orthopedic foot and ankle surgery, for conditions including osteoarthritis, instability, and others. The surgery is frequently performed as part of a double or triple arthrodesis. Multiple surgical constructs have been described, including screws, plate/screw constructs, and staple/screw constructs. Few studies exist that specifically focus on the talonavicular joint, and those that do are often limited by low patient volumes. Studies that do study non-union of the talonavicular joint do not offer comparative data on non-union rates between the different methods of fixation. The purpose of this study was to determine the rate of arthrodesis in talonavicular fusion surgery among different fixation techniques and determine if hardware has a significant effect on union rate. Methods: This study is a retrospective single institution, multi-surgeon study evaluating arthrodesis rates in the talonavicular joint. Adult patients undergoing primary talonavicular fusion (isolated or as part of double/triple arthrodesis) from 2015-2018 with a minimum of 3 month radiographic follow-up were studied. Patients undergoing revision talonavicular fusion or fusion as part of Charcot reconstruction were excluded. Patient radiographic and chart notes were reviewed to assess fixation type (single screw, 2-hole compression plate, screw + staple, or 4-hole plate), the status of the arthrodesis at >=3 months and any hardware complications or reoperations following the index procedure. Descriptive statistics were generated for standard patient demographics and co-morbidities. Non-union rates were calculated for the cohort as a whole and for each fixation technique utilized along with the frequency of hardware complications/removal. Univariate analysis was performed to determine risk factors for increased non-union rate, including patient demographics, co-morbidities, and fixation technique. Results: A total of 101 patients were included. Hardware included 69 single screws, 27 two-hole compression plates, and 4 screw + staple constructs. Four patients (3.96%) went on to develop a nonunion of the talonavicular joint, while 10 patients (9.9%) required a removal of hardware procedure following the initial arthrodesis. Of nonunion cases, 3 patients had single screw hardware while 1 had a two-hole plate. Removal of hardware was necessary in 5/69 patients with single screws (7.2%) and 4/27 patients with 2-hole plates (14.8%). Statistical significance could not be concluded when comparing union vs. nonunion patients due to the success of union across hardware groups that resulted in a scarce nonunion patient population (4 patients). Conclusion: This study demonstrates that there are multiple types of hardware appropriate for achieving and maintaining talonavicular fusion. One limitation of this report is that the majority of non-single screw cases utilized a 2-hole plate, with significantly fewer patients utilizing screw + staple and 4-hole plate constructs. Single screw and 2-hole plate hardware techniques achieve excellent rate of union, and physicians can make decisions of which to utilize based on patient factors. Further study is indcated on even larger patient cohorts with increased population of nonunion cases so that significant patient risk factors for nonunion of the joint can be identified.